Limbo and the Children of Faerie - Pinsent, A (Philosophy Documentation Center, 2016)
The fate of the ungraced innocents highlights much of what has been most difficult about the doctrine of original sin. As an alternative to the extremes of an easy-going universalism or consignment to the fires of hell, this paper reexamines Aquinas’s claims about a possible state of ungraced natural flourishing, arguing that this state is richer and more interesting than the name ‘limbo’ implies. The paper also applies recent work in philosophy and psychology, especially on the second-person perspective, to understand better the state of those in limbo, who might be better called the ‘children of faerie’. It concludes by examining the possible relationship of the children of faerie and the children of God in a post-resurrection state.